Preparation method and application of comfortable composition
By preparing a comfort-promoting composition, combined with a super acid catalyst, organic sunscreen agent dispersion, polydimethylsiloxane and hydrated alumina dispersion slurry, it solves the problem that sunscreen skin care products in the existing technology have difficulty in balancing high sun protection index and long wavelength. The issues of UV protection index and skin comfort achieve an efficient, comfortable and non-allergic sunscreen effect.
Patent Information
- Application Number
- CN202411900791.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The prior art is difficult to provide sun protection products that are comfortable and not prone to allergies while providing high sun protection index and long-wave UV protection index, especially in high-intensity outdoor activities.
By preparing a cooling composition, the composition includes ultra -strong acid catalysts, organic sunscreen dispersed materials, wrapped clustering polyckal silicide, hydraulic oxide dispersed pulp, and smooth reflection inorganic powder Combined with the whale wax PEG/PPG-10/1 polymailing silicone and vulgar palmate, it forms a stable suspension to improve the sunscreen effect and experience of the product.
While realizing the high sunscreen index and long -wave ultraviolet protection index, it provides the effect of comfortable skin and is not easy to allergic. It is suitable for high -intensity outdoor activities and has skin care effects.
Smart Images

Figure CN119326672A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of daily chemical skin care products, and in particular to a preparation method and application of a refreshing composition that can be used in skin care products. Background Art
[0002] As people's living standards improve, consumers pay more and more attention to outdoor activities. However, how to prevent skin damage from ultraviolet rays while enjoying the sun is an urgent problem to be solved.
[0003] At present, the combination of organic synthetic sunscreen and inorganic sunscreen products meet the above needs because of their quick effect and good durability. However, organic sunscreens are affected by human secretions and light environment, have a relatively short action time, and feel sticky and heavy on the skin, making them difficult to adapt to high-intensity outdoor activities, and they always have the risk of skin allergies; inorganic sunscreens with nano titanium dioxide and nano zinc oxide as the main ingredients have a long sun protection period, but the relative effect is not as good as organic sunscreens, and the cosmetics market is more sensitive to the concept of nano in skin care products, restrictive regulations are frequently issued, and production standards need to be adjusted differently; in addition, in the preparation process of products containing nano components, the limitations of dispersion conditions make the products easy to form agglomerations and appear granular, which presents an unpleasant astringent feeling on the skin, especially for high sun protection index products. The discomfort after application often makes consumers (especially those with allergies) feel distressed.
[0004] In order to solve the above problems, the industry has used smooth ingredients such as aluminum starch octenylsuccinate, lauroyl lysine, modified mica, cyclopentasilicone and dimethicone and their combinations as additives to explore the anti-allergic and skin feel enhancement of the above organic / inorganic sunscreen skin care products. However, so far, there is still no sunscreen skin care product with a high SPF / UVB protection index that feels comfortable and does not cause allergies. Summary of the invention
[0005] The first technical problem to be solved by the present invention is to provide a method for preparing a refreshing composition that can significantly reduce the irritation of organic sunscreens and the unpleasant astringency of inorganic sunscreens to meet the needs of allergic physiques based on the current status of the prior art.
[0006] The second technical problem to be solved by the present invention is to provide an application of the above-mentioned refreshing composition in view of the current status of the prior art, which is used in sunscreen skin care products. The sunscreen skin care products can be efficiently absorbed, and the skin feels refreshing after application, is not prone to allergies, and has a skin care effect.
[0007] The third technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned sunscreen skin care product in view of the current status of the prior art.
[0008] The technical solution adopted by the present invention to solve at least one of the above technical problems is: A method for preparing a refreshing composition comprises the following steps: (1) Preparation of superacid catalyst Phosphorus pentoxide and crystalline aluminum sulfate are uniformly mixed and calcined to obtain a super acid catalyst; (2) Preparation of organic sunscreen dispersion Ethylhexyl methoxycinnamate, butyl octanol salicylate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazone, and dibasic acid ester are heated and uniformly mixed with butyl hydroxytoluene to obtain a feed liquid A; (3) Preparation of encapsulated polydimethylsiloxane The octamethylcyclotetrasiloxane and the above-mentioned feed liquid A are stirred and mixed to obtain feed liquid B; The material liquid B is reacted with a super acid catalyst and hexamethyldisiloxane in sequence to obtain a coated polydimethylsiloxane finished liquid, which is named as material liquid C; (4) Preparation of hydrated alumina dispersion slurry The high-purity sodium aluminum carbonate and the sodium hydroxide aqueous solution are reacted to obtain a hydrated aluminum oxide dispersion slurry containing sodium aluminate, which is named as liquid D; (5) Preparation of smooth modified inorganic powder Nano-sized titanium dioxide and nano-sized zinc oxide are added to the liquid D in batches, and a layer of gel Al(OH) is deposited on the surface of the nano-sized titanium dioxide and zinc oxide particles. 3 After further post-treatment, a modified nano-scale titanium dioxide / zinc oxide smooth inorganic sunscreen powder uniformly loaded with a composite structure of gel aluminum hydroxide / γ-aluminum oxide was obtained, which was named powder E; (6) Preparation of refreshing composition Powder E is added into liquid C, and cetyl PEG / PPG-10 / 1 polydimethylsiloxane and dextrin palmitate are added, and the mixture is stirred to obtain the target product, a refreshing composition.
[0009] Preferably, the preparation method of the refreshing composition comprises the following steps: (1) Preparation of superacid catalyst Phosphorus pentoxide and crystalline aluminum sulfate are mixed in a certain proportion (ensuring that the ratio of phosphorus to sulfur in the final product is 1:0.5-0.7), dispersed into fine powder in liquid carbon dioxide by ultrasonic wave, returned to room temperature within 1 hour, and reacted for at least 5 hours under fast mixing conditions; the mixture after the preliminary reaction is transferred to a high-temperature furnace, and heated to 150-160°C within 1 hour, dehydrated for 2 hours, and then heated to 850-880°C within 2 hours, calcined for at least 3 hours, so that the mixture fully reacts and generates a super acid catalyst; the product is naturally cooled to room temperature and granulated to obtain micron-sized fine particles; (2) Preparation of organic sunscreen dispersion Mix the organic sunscreen agents ethylhexyl methoxycinnamate, butyl octanol salicylate, bis-ethylhexyloxyphenol methoxyphenyl triazine, and ethylhexyl triazone, disperse them in 1 to 1.5 times the amount of dibasic acid ester, heat to 50 to 60° C. to make the materials homogeneous, add butylated hydroxytoluene, an antioxidant, in an amount of 0.5% to 0.8% of the total amount of the materials, mix well and set aside to obtain liquid A; (3) Preparation of encapsulated polydimethylsiloxane 40-60 parts by weight of octamethylcyclotetrasiloxane and 30-50 parts by weight of the above-mentioned liquid A are stirred for 20-30 minutes to obtain liquid B; Under stirring conditions, 4-5 parts by weight of the superacid catalyst are added to liquid B, and the temperature is controlled at 60-65° C. and stirred for 6-8 hours to obtain a terminal hydroxyl polydimethylsiloxane coated with an organic sunscreen agent. Then, 5-10 parts by weight of hexamethyldisiloxane are added, and the temperature is controlled at 60-70° C. and stirred for 2-3 hours to obtain a crude product liquid of polydimethylsiloxane coated with a sunscreen agent; 200-300 parts by weight of purified water are added, and the mixture is rapidly stirred for 20-30 minutes and then washed. The mixture is allowed to stand for 2-3 hours and separated, and the lower aqueous phase is discarded to remove impurities such as the catalyst. The upper layer material is dehydrated and the hexamethyldisiloxane low-boiling products are dehydrated at 0.01 MPa at 60-70° C. for 1.5-3 hours to obtain a finished polydimethylsiloxane solution coated with a sunscreen agent, which is named liquid C; (4) Preparation of hydrated alumina dispersion slurry 5-10 parts by weight of high-purity white powder of sodium aluminum carbonate (wherein the mass content of aluminum oxide is 40%) are added to 50-100 parts by weight of a sodium hydroxide aqueous solution with a volume concentration of 2%-5% under stirring conditions, and stirred at 70-80°C for 1-2 hours until the system becomes nearly transparent to obtain a hydrated aluminum oxide dispersion slurry containing sodium aluminate, which is named feed liquid D; (5) Preparation of smooth modified inorganic powder The feed liquid D is added with nano-sized titanium dioxide and nano-sized zinc oxide in batches under the condition of bubbling with high-purity carbon dioxide, and gel Al(OH) is deposited on the surface. 3 The nano-sized titanium dioxide and zinc oxide particles are sequentially dehydrated, dissociated and homogenized to obtain the powder E; more specifically: Under stirring conditions, 5-10 parts by weight of nano-sized titanium dioxide and 3-8 parts by weight of nano-sized zinc oxide were added to the above-mentioned hydrated aluminum oxide dispersion slurry D in batches, the temperature was controlled at 60-70°C, high-purity carbon dioxide was bubbled into the bottom of the reactor in multiple ways, and the reaction was carried out for 15-20 hours to make the pH value of the material reach 7.2-7.5, and a layer of gel Al(OH)2O3 was deposited on the surface of the nano-sized titanium dioxide and zinc oxide particles. 3, composite particles with micron particle size were obtained; after completion, the solution was dehydrated by plate and frame filter pressing, and then transported to colloid mill JML-50 for treatment 3 times, dried in an oven at 90-100°C for 1-2 hours, and then roasted at 450-550°C for 0.5-1 hour, and then dissociated and homogenized by impact of 0.6-0.9MPa high-pressure airflow to obtain a modified micron-sized titanium dioxide / nano-sized zinc oxide smooth inorganic sunscreen powder uniformly loaded with a composite structure of gel aluminum hydroxide / γ-aluminum oxide fusion, named powder E; (6) Preparation of refreshing composition 13-28 parts by weight of the above-mentioned smooth modified inorganic sunscreen powder E are dispersed and added into 50-90 parts by weight of the sunscreen coated polydimethylsiloxane finished product liquid C under stirring conditions, 1-3 parts by weight of cetyl PEG / PPG-10 / 1 polydimethylsiloxane are added, the mixture is heated to 60-70°C after being mixed well, the speed is controlled to 280-350 rpm and stirred for at least 2 hours until it becomes a homogeneous and highly viscous state, 0.3-0.5 parts by weight of dextrin palmitate are dispersed and added, the speed is controlled to 80-120 rpm and stirred for at least 1 hour, and the target product, a refreshing composition, is obtained.
[0010] Preferably, in step (1), the mass ratio of phosphorus to sulfur in the obtained superacid catalyst is 1:(0.5-0.7).
[0011] Preferably, in step (2), the mass ratio of ethylhexyl methoxycinnamate, butyl octanol salicylate, bis-ethylhexyloxyphenol methoxyphenyl triazine and ethylhexyl triazone is 8:(5-6):(2.5-3):(1.5-2); the dibasic acid ester is a mixture of dibutyl adipate and diisopropyl sebacate, and the mass ratio of dibutyl adipate to diisopropyl sebacate is 6:(5-8).
[0012] Preferably, the refreshing composition comprises the following components: Powder E 13~28 parts by weight, Liquid C 50~90 parts by weight, 1-3 parts by weight of cetyl PEG / PPG-10 / 1 polydimethylsiloxane, Dextrin palmitate 0.3-0.5 parts by weight.
[0013] Preferably, the powder E is prepared from the following components: Liquid D 55~110 parts by weight, 5-10 parts by weight of nano-sized titanium dioxide, 3-8 parts by weight of nano zinc oxide; Wherein, the feed liquid D is prepared from the following components: High-purity sodium aluminum carbonate (high-purity sodium aluminum carbonate is white powder, and the mass content of aluminum oxide converted into aluminum oxide is 40%) 5-10 parts by weight, 50 to 100 parts by weight of an aqueous sodium hydroxide solution having a volume concentration of 2% to 5%.
[0014] Preferably, the feed liquid C is prepared from the following components: Liquid B 70~110 parts by weight, 4 to 5 parts by weight of superacid catalyst, 5-10 parts by weight of hexamethyldisiloxane, 200-300 parts by weight of water; Wherein, feed liquid B is prepared from the following components: Liquid A 30~50 parts by weight, 40-60 parts by weight of octamethylcyclotetrasiloxane.
[0015] A sunscreen skin care product using the refreshing composition comprises the following components in parts by weight: 45-55 parts of refreshing composition, 1-3 parts of vinyl dimethicone / methylsiloxane silsesquioxane crosspolymer, 1~2 parts of cetyl PEG / PPG-10 / 1 polydimethylsiloxane, 2-3 parts of diethylamino hydroxybenzoyl hexyl benzoate, 2~4 parts of triethoxycaprylylsilane, 1~3 parts of isostearic acid, 4-7 parts of butanediol, 2-3 parts of methyl methacrylate cross-linked polymer, 1-3 parts of disteardimethylammonium hectorite, 1~2 parts of triethyl citrate, VP / hexadecene copolymer 0.5-0.8 parts, PEG-10 polydimethylsiloxane 1~3 parts, Phenoxyethanol 0.1~0.3 parts, 1~2 parts of ethylhexylglycerin, 1,3-propylene glycol 1~2 parts, 0.3~0.6 parts of MAGNOLIA BIONDII extract, 0.1~0.3 parts of bisabolol, 0.1~0.2 parts of dipotassium glycyrrhizinate, 0.2~0.3 parts of p-hydroxyacetophenone, 0.1-0.2 parts of tetrahydromethylpyrimidine carboxylic acid, Xanthan gum 0.08~0.12 parts, 20~25 parts of water.
[0016] A method for preparing the above-mentioned sunscreen skin care product comprises the following steps: (1) Vinyl dimethicone / polymethicone silsesquioxane crosspolymer and cetyl PEG / PPG-10 / 1 dimethicone are mixed and stirred until uniformly mixed, and diethylamino hydroxybenzoyl hexyl benzoate is added, and stirred and mixed until uniformly mixed at room temperature to obtain an oil phase G; Triethoxycaprylylsilane, triethyl citrate and isostearic acid are stirred and mixed and heated to 60-65°C and stirred and mixed to form a liquid state, VP / hexadecene copolymer and methyl methacrylate cross-linked polymer are added in batches and stirred and mixed for at least 1 hour until a homogeneous thick liquid state is formed, dispersing disteardimethylammonium hectorite and stirring and mixing for at least 2 hours until a homogeneous state is formed, and then adding it to the refreshing composition, controlling the rotation speed at 200-300 rpm and stirring for at least 3 hours until a homogeneous high viscosity state is formed, to obtain oil phase H; (2) Add PEG-10 polydimethylsiloxane to two-thirds of the total amount of water under stirring and dissolve until it becomes translucent. Add dipotassium glycyrrhizinate and stir until it becomes nearly transparent. Add phenoxyethanol ethylhexylglycerin and p-hydroxyacetophenone and heat to 60-70°C for use to obtain aqueous phase I. (3) Disperse xanthan gum in 1,3-propylene glycol and butylene glycol, stir until it becomes nearly transparent and highly viscous, add one third of the total amount of water, mix well, add tetrahydromethylpyrimidine carboxylic acid, MAGNOLIA BIONDII extract and bisabolol, mix well and set aside to obtain aqueous phase J; (4) Under stirring conditions, control the temperature at 60-75°C, slowly add the aqueous phase I into the oil phase H, and stir for at least 10 minutes until the system reaches the initial state of a high-viscosity W / O emulsion. Then control the speed at 3000-5000 rpm for homogenization for at least 15 minutes to obtain a homogenous high-gloss and high-viscosity W / O emulsion. Cool to 35-38°C, add the aqueous phase J under stirring conditions, and then control the speed at 3000-5000 rpm for homogenization for at least 10 minutes until it reaches a high-gloss homogenous emulsion state. Then add the oil phase G, control the speed at 300-400 rpm for stirring for at least 30 minutes, homogenize the high-gloss and high-viscosity W / O emulsion, and age it for 24 hours to obtain the target product, a sunscreen skin care product.
[0017] Compared with the prior art, the advantages of the present invention are as follows: the present invention utilizes the unique properties of polyorganosiloxane chains that are easily induced into a helical structure and the encapsulation and anti-inflammatory and smoothing properties of the composite structure of gel aluminum hydroxide / γ-aluminum oxide fusion, thereby greatly reducing the contact between organic sunscreens that have a risk of causing skin allergies and inorganic sunscreens that are likely to cause an unpleasant astringent feeling on the skin, and combines with skin care functional substances to formulate a sunscreen care product with a high sun protection index / long-wave ultraviolet protection index that has a comfortable skin feel and is not prone to allergies, achieving both sun protection and beauty benefits.
[0018] The specific mechanism of the present invention is described in detail as follows: (1) In organosiloxane compounds, the empty 3d orbital on Si in the Si-O bond forms a dπpπ covalent bond with the non-covalent electron pair of the O atom, making the Si-O bond partially double bonded and more active. The longer the bond length of the Si-O bond, the less steric hindrance to the rotation of the side group, making it more vulnerable to attack. The electronegativity difference between Si and O is large, and the Si-O bond is 50% ionic, making polyorganosiloxane very sensitive to reactions with ionic properties. The bond angle of the Si-O bond is large, making it easy for the Si-O bonds to rotate. Due to the mutual compensation of the dπpπ bonds between Si-O and the mutual compensation between the Si-O dipoles, the polyorganosiloxane chain forms a helical structure. Each spirocycle consists of about 6 silicon-oxygen chain segments, with the methyl group facing outward, acting as a shield (see Figure 1 ). The specific arrangement of the molecular chains of dimethylsiloxane during the polymerization process maintains a balance between rigidity and flexibility, as well as the intermolecular interaction forces (such as van der Waals forces, hydrogen bonds, etc.), so that the main chain of polydimethylsiloxane can also form a more complex three-dimensional structure including a helical structure. This type of structure with embedding characteristics makes it very easy to wrap up the electron cloud offset polar organic compounds and organic sunscreens containing delocalized π bonds, including ethylhexyl methoxycinnamate, butyloctanol salicylate, bis-ethylhexyloxyphenol methoxyphenyl triazine, and ethylhexyl triazone during the further polymerization process. In addition, this type of organic sunscreen is an oil-soluble substance and has a certain compatibility with polydimethylsiloxane in chemical properties. It can be more easily embedded by polydimethylsiloxane. Polydimethylsiloxane can be used as a carrier or matrix to evenly disperse the organic sunscreen in cosmetics, thereby improving the sunscreen effect and usage experience of the product, and minimizing the chance of direct contact between irritating organic sunscreens and the skin.
[0019] (2) Nano-sized titanium dioxide and zinc oxide are used as physical sunscreens in sunscreen cosmetics and have high UV shielding efficiency. However, due to their small particles, large specific surface area and extremely high surface energy, they are easy to form aggregates, which affects the dispersion and transparency of the product. At the same time, the electron-hole pairs generated after absorbing ultraviolet rays may cause the product to change color and have odor. Gel aluminum hydroxide / γ-aluminum oxide fusion as a coating material has many properties that are beneficial to the skin. Its astringency helps reduce the greasiness and discomfort of the skin by absorbing excess moisture on the skin surface. Its antipruritic effect is because it reduces irritation and relieves skin itching symptoms by combining with acidic substances on the skin surface. Its antipruritic effect also has an anti-inflammatory effect by neutralizing acidic substances on the skin surface and reducing the release of inflammatory mediators.
[0020] When nano-sized titanium dioxide and zinc oxide are coated with gelled aluminum hydroxide / γ-aluminum trioxide fusion, the aggregation of nanoparticles can be reduced, thereby improving their dispersibility in cosmetics. The coating layer can protect the nanoparticles from the influence of the external environment, such as light, humidity, etc., thereby improving their stability. The astringent, antipruritic and anti-inflammatory effects of gelled aluminum hydroxide in the fusion may help reduce the adverse stimulation of nanoparticles to the skin. Gelled aluminum hydroxide has excellent oil absorption and hygroscopicity, which can effectively absorb oil and sweat on the surface of the skin, keeping the skin fresh and dry. This property allows cosmetics containing gelled aluminum hydroxide to reduce the greasy feeling of the skin and make the makeup more durable and fresh. Gelled aluminum hydroxide can help adjust the viscosity of cosmetics, making its texture lighter and smoother, easier to spread evenly, and not produce a heavy feeling. This regulating effect makes the cosmetics smoother when applied, and it is not easy to pull the skin, thereby reducing irritation and damage to the skin. The microparticle structure of gelled aluminum hydroxide can increase the slipperiness between the skin and the cosmetics, making the application process easier and more pleasant. This smooth feeling not only improves the user experience, but also helps to evenly distribute cosmetics on the skin. Gel aluminum hydroxide is a chemically stable substance that is not easy to react chemically with the skin and will not cause irritation or allergies to the skin. At the same time, due to its moderate molecular size, it will not clog pores, further reducing the potential risk to the skin. The skeleton structure formed by nano-scale titanium dioxide and zinc oxide coated with gel aluminum hydroxide / γ-aluminum trioxide fusion can provide certain support and stability, so that the crushed fine powder forms a uniform coating on the skin. This coating can reduce the direct contact area between titanium dioxide and zinc oxide nanoparticles and the skin, thereby reducing astringency and other adverse reactions. The smooth modified inorganic sunscreen powder containing the composite structure of gel aluminum hydroxide / γ-aluminum trioxide fusion not only maintains excellent physical sunscreen efficacy, but also greatly increases the anti-allergic and comfort of the composite powder.
[0021] (3) Nano-sized titanium dioxide and nano-sized zinc oxide coated and modified by gel aluminum hydroxide / γ-aluminum oxide fusion can be evenly dispersed in silicone oil to form a stable suspension, which helps to reduce the aggregation and deposition of nanoparticles on the skin, thereby reducing the unpleasant astringency. Silicone oil has excellent lubricity and compatibility, and can form a good interface interaction with the coated and modified nanoparticles, which helps to form a more delicate and uniform coating, better adapt to the skin surface, reduce the friction between the inorganic powder particles and the skin, and further reduce the astringency.
[0022] (4) Magnolia biondii extract is used as an active ingredient in cosmetics and skin care products, especially in sun protection and after-sun repair, showing excellent efficacy. Magnolia biondii extract is rich in lignans and can provide effective protection before the skin is sunburned. By targeting and regulating the damage-associated molecular patterns (DAMPs) of sunburned cells, it inhibits the release of various cytokines, thereby reducing the skin's sensitivity to ultraviolet rays. When the skin is damaged by ultraviolet rays, Magnolia biondii extract can accelerate the disappearance of erythema and reduce the inflammatory response of the skin. Its soothing and repairing effects help restore the skin to a healthy state. Products containing Magnolia biondii extract, such as sunscreen, spray, gel, etc., can help increase the SPF value and provide more comprehensive protection for the skin. Magnolia biondii extract has a significant soothing effect and can reduce discomfort such as redness and stinging of the skin. For sensitive skin, it is a very gentle skin care ingredient. Magnolia biondii extract can also be added as an efficacy adjuvant to sunscreen and whitening products to enhance the overall effect of the product.
[0023] (5) Ectoin, also known as ectoin, is an amino acid derivative with multiple functions. Ectoin can effectively isolate ultraviolet rays, fight photoaging, and prevent DNA and cell damage caused by ultraviolet rays. It has a significant repair effect on skin cell DNA damage caused by ultraviolet rays.
[0024] One ectoine molecule can complex multiple free water molecules in the skin, so that the free water in the skin cells is structured and continuously locked in moisture, thereby maintaining the balance of skin osmotic pressure. Because of its small molecular size, easy absorption and solubility in water, it can significantly increase the moisture content of the skin. The higher the concentration, the faster the increase in skin moisture content. In extreme environments such as high temperature, high salt, and strong ultraviolet rays, ectoine can maintain a good active state and protect cells. It can also stabilize the structure of enzyme proteins in organisms to ensure that the molecules in cells can function normally. Ectoine can enhance the immune protection ability of skin cells and increase the ability to repair cells. It is also very strong in fighting microorganisms and allergens, and also has good anti-allergic and anti-inflammatory functions. Ectoine can enhance the activity of fibroblasts, thereby promoting the production of hyaluronic acid, collagen and elastic fibers. In short, ectoine is mainly used as an antioxidant and skin conditioner in cosmetics, with multiple functions such as skin rejuvenation, anti-aging, moisturizing, sun protection, repair, anti-inflammatory and soothing.
[0025] Bisabolol and dipotassium glycyrrhizinate are also excellent in anti-allergic and soothing effects.
[0026] The various skin-nourishing, anti-allergic and soothing substances of the present invention work synergistically to obtain a sunscreen product with a high sun protection index / ultraviolet long wave protection index that is comfortable on the skin and does not cause allergies. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a structural diagram in the inventive content of the present invention. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below with reference to the embodiments.
[0029] Embodiment 1:
[0030] The preparation method of the refreshing composition in this embodiment is as follows: (1) Preparation of superacid catalyst: 5000 g of phosphorus pentoxide and 6700 g of anhydrous aluminum sulfate were mixed (the phosphorus-sulfur ratio in the final product was 1:0.6), dispersed into fine powder in liquid carbon dioxide by ultrasonic wave, returned to room temperature within 1 hour, and reacted for 6 hours under fast mixing conditions. The mixture after the initial reaction was transferred to a high-temperature furnace, heated to 155°C within 1 hour, dehydrated for 2 hours, and then heated to 860°C within 2 hours, calcined for 3 hours, so that the mixture fully reacted and a superacid catalyst was generated. The product was naturally cooled to room temperature and granulated into 10 micron fine particles.
[0031] (2) Preparation of organic sunscreen dispersion: In a 50-liter stainless steel mixing pot with stirring (jacket heating), add 10 kg of dibutyl adipate and 10 kg of diisopropyl sebacate, stir to form a mixed liquid, then add 8 kg of organic sunscreen ethylhexyl methoxycinnamate, 6 kg of butyl octanol salicylate, 2.5 kg of bis-ethylhexyloxyphenol methoxyphenyl triazine, and 1.5 kg of ethylhexyl triazone, stir to mix evenly, heat to 55°C to make the material homogeneous, add 2.3 kg of antioxidant butyl hydroxytoluene, mix well and set aside, named feed liquid A, totaling 38 kg.
[0032] (3) Preparation of encapsulated polydimethylsiloxane: 45 kg of octamethylcyclotetrasiloxane and 38 kg of the above-mentioned liquid A were added into a 100-liter high-quality stainless steel mixing pot with stirring, and stirred for 25 minutes to mix, a total of 83 kg, to obtain liquid B; In a 200-liter high-quality stainless steel reaction pot with stirring (with a large area refrigeration device and receiver), 83 kg of liquid B was added under stirring conditions (speed control 120rpm), and then 5 kg of the above-mentioned superacid catalyst was added, and the temperature was controlled at 62℃ and stirred for 6 hours to obtain the terminal hydroxyl polydimethylsiloxane coated with organic sunscreen agent. Then 6 kg of hexamethyldisiloxane was added, and the temperature was controlled at 62℃ and stirred for 3 hours to obtain the crude product liquid of polydimethylsiloxane coated with sunscreen agent. 100 kg of purified water was added, and the mixture was quickly stirred for 25 minutes for washing, and then the mixture was allowed to stand for 3 hours to separate. The lower aqueous phase was discarded to remove impurities such as catalysts. The upper layer of the material was dehydrated and low-boiling substances were removed at 60℃ for 3 hours under 0.01MPa to obtain the finished product liquid of polydimethylsiloxane coated with sunscreen agent, totaling 88 kg, named liquid C.
[0033] (4) Preparation of hydrated alumina dispersion slurry: In a 100-liter high-quality stainless steel reaction pot with stirring, 60 kg of 3% sodium hydroxide aqueous solution was added, and 8 kg of high-purity white powder of sodium aluminum carbonate with a content of 40% aluminum sesquioxide was sprinkled in three batches. The mixture was reacted at 72°C with stirring at 80 rpm for 2 h. The system was almost transparent, and 68 kg of hydrated alumina dispersion slurry containing sodium aluminate was obtained, which was named liquid D.
[0034] (5) Preparation of smooth modified inorganic powder: In the above 100 liter high-quality stainless steel reactor with stirring, 6 kg of nano-sized titanium dioxide and 4 kg of nano-sized zinc oxide were added into the above hydrated alumina dispersion slurry D in five batches under the condition of controlled stirring at 180 rpm. The temperature was controlled at 60-70°C. High-purity carbon dioxide was bubbled into the bottom of the reactor in multiple ways. The reaction was carried out for 18 hours to make the pH value of the material reach 7.3. A layer of gel Al(OH) was deposited on the surface of the nano-sized titanium dioxide and zinc oxide particles. 3 , and composite particles with a particle size of about 50 microns were obtained. After completion, the solution was dehydrated by plate and frame filter pressing, and then transported to the colloid mill JML-50, treated under the action of mechanochemical force, dried in an oven at 100℃ for 1h, and then roasted at 500℃ for 0.5h, and then dissociated and homogenized by 0.6MPa high-pressure air flow impact, and 18 kg of a uniformly loaded gel aluminum hydroxide / γ-aluminum oxide fusion composite structure modified nano-scale titanium dioxide / zinc oxide smooth inorganic sunscreen powder was obtained, named powder E.
[0035] (6) Preparation of refreshing composition: In a 120-liter high-quality stainless steel reaction pot with stirring, add 88 kg of sunscreen polydimethylsiloxane coated finished liquid C, sprinkle 18 kg of the above-mentioned smooth modified inorganic sunscreen powder E in three batches, mix well, add 2 kg of spermaceti PEG / PPG-10 / 1 polydimethylsiloxane, raise the temperature to 62°C after mixing well, control the speed at 280 rpm and stir for 3 h until it becomes a homogeneous and highly viscous state, disperse 0.4 kg of dextrin palmitate, control the speed at 100 rpm and stir for 1 h, cool to room temperature to obtain a high-efficiency sunscreen skin care product refreshing composition, totaling 108.5 kg.
[0036] Embodiment 2: The preparation method of the sunscreen skin care lotion in this embodiment is: formula: 50 kg of the refreshing composition of Example 1, Vinyl Dimethicone / Methicone Silsesquioxane Crosspolymer 1kg, Cetyl PEG / PPG-10 / 1 Polydimethylsiloxane 2 kg, 3 kg of diethylaminohydroxybenzoyl hexyl benzoate, 2 kg of triethoxycaprylylsilane, Isostearic acid 1 kg, 4 kg of butanediol, Methyl Methacrylate Crosspolymer 3 kg, 3 kg of disteardimethylammonium hectorite, 2 kg of triethyl citrate, VP / hexadecene copolymer 0.6 kg, PEG-10 Dimethicone 2kg, Phenoxyethanol 0.3 kg, Ethylhexylglycerin 2 kg, 1,3-propylene glycol 2 kg, MAGNOLIA BIONDII flower extract 0.6 kg, Bisabolol 0.2 kg, Dipotassium glycyrrhizinate 0.2 kg, 0.3 kg of p-hydroxyacetophenone, Tetrahydromethylpyrimidine carboxylic acid 0.2 kg, Xanthan gum 0.1 kg, 24 kg of purified water, The above materials are all commercially available products and are cosmetic grade.
[0037] Process conditions and operation steps: (1) In a 10-liter stainless steel mixing pot with a stirrer, add 1 kg of vinyl dimethicone / polymethicone silsesquioxane crosspolymer and 2 kg of cetyl PEG / PPG-10 / 1 dimethicone, stir to mix evenly, add 3 kg of diethylaminohydroxybenzoyl hexyl benzoate in three batches, stir to mix evenly at room temperature, and obtain 6 kg of oil phase G in total.
[0038] In a 15-liter stainless steel mixing pot with stirring (jacket heating), 2 kg of triethoxyoctylsilane, 2 kg of triethyl citrate and 1 kg of isostearic acid were added, mixed and heated to 62°C, stirred and dissolved to form a liquid state, 3 kg of VP / hexadecene copolymer and methyl methacrylate cross-linked polymer were added in batches, stirred for 1 hour to mix and form a homogeneous viscous liquid state, 3 kg of disteardimethylammonium hectorite was sprinkled in three batches, stirred for 2 hours to mix and form a homogeneous state, and then the materials were pumped into a 100-liter stainless steel mixing pot with stirring (jacket heating) containing 50 kg of Example 1. High-efficiency sunscreen skin care product refreshing composition F, the temperature was controlled at 62°C, the speed was controlled at 200-300 rpm, and stirred for 3 hours until it was a homogeneous and highly viscous state, to obtain the oil phase H, a total of 61 kg.
[0039] (2) In a 30-liter stainless steel mixing pot with stirring (jacket heating), add 16 kg of purified water, add 2 kg of PEG-10 polydimethylsiloxane under stirring and dissolve until it becomes translucent, add 0.2 kg of dipotassium glycyrrhizinate and stir until it becomes almost transparent, add 0.3 kg of phenoxyethanol, 2 kg of ethylhexylglycerin and 0.3 kg of p-hydroxyacetophenone, raise the temperature to 60-70°C and set aside to obtain aqueous phase I, totaling 20.8 kg.
[0040] In a 20-liter stainless steel mixing pot with stirring (jacket heating), add 2 kg of 1,3-propylene glycol and 4 kg of butylene glycol, stir evenly, add 0.1 kg of xanthan gum in three batches, mix until it becomes almost transparent and highly viscous, add 8 kg of purified water, mix evenly, add 0.2 kg of tetrahydromethylpyrimidine carboxylic acid, 0.6 kg of MAGNOLIA BIONDII extract and 0.2 kg of bisabolol, mix evenly and set aside to obtain aqueous phase J, a total of 15.1 kg.
[0041] (3) In a 150-liter stainless steel homogenizing emulsifier with stirring (equipped with a homogenizer at the bottom), first pump in 61 kg of oil phase H under stirring conditions (control speed at 50 rpm), control the temperature to 70°C, slowly pump in 20.8 kg of water phase I within 10 minutes, stir for 15 minutes until the system is in the initial state of high-viscosity W / O emulsion, then control the speed at 5000 rpm for homogenization for 25 minutes to obtain a homogenous high-gloss and high-viscosity W / O emulsion, cool to 37°C, and pump in 15.1 kg of water phase J under stirring conditions (control speed at 100 rpm), then control the speed at 3000 rpm for homogenization for 10 minutes, stir until it is in the state of high-gloss homogenous emulsion, then pump in 6 kg of oil phase G, control the speed at 300-400 rpm for stirring for 40 minutes, homogenize the high-gloss and high-viscosity W / O emulsion, and age it for 24 hours to obtain a high-efficiency sunscreen skin care lotion product, totaling 103 kg.
[0042] Comparative Example 1: Preparation of physical composition of sunscreen silicone oil: By bypassing the process of preparing silicone oil by co-polymerizing octamethylcyclotetrasiloxane with an organic sunscreen agent, the organic sunscreen agent is directly physically mixed with a theoretically converted amount of dimethyl silicone oil and a carrier ester. At the same time, the process of embedding nano inorganic sunscreen agent particles with a composite structure of gel aluminum hydroxide / γ-aluminum trioxide fusion is deleted, and a theoretically converted amount of aluminum hydroxide fine powder is directly physically mixed with nano titanium dioxide and nano zinc oxide. Referring to the formula of Example 1 (scaled down), a sunscreen agent silicone oil physical composition is prepared, as described in detail as follows: (1) Preparation of organic sunscreen dispersion: In a 50 ml stainless steel mixing cup with stirring (jacket heating), add 10 g of dibutyl adipate and 10 g of diisopropyl sebacate, stir to form a mixed solution, then add 8 g of organic sunscreen ethylhexyl methoxycinnamate, 6 g of butyl octanol salicylate, 2.5 g of bis-ethylhexyloxyphenol methoxyphenyl triazine, and 1.5 g of ethylhexyl triazone, stir to mix, heat to 55°C to make the material homogeneous, add 2.3 g of antioxidant butyl hydroxytoluene, mix well and set aside, named feed solution A, totaling 38 g.
[0043] (2) Preparation of organic sunscreen polydimethylsiloxane physical blending liquid: 45 g of dimethyl silicone oil and 38 g of the above-mentioned liquid A were added into a 100 ml high-quality stainless steel mixing cup with stirring, and stirred for 25 minutes to mix, a total of 83 kg, to obtain liquid B; In a 200 ml high-quality stainless steel mixing cup with stirring, add 83 grams of liquid B under stirring conditions (control the speed at 120 rpm), then add 6 grams of dimethyl silicone oil, control the temperature at 42°C and stir for 1 hour to obtain an organic sunscreen agent polydimethylsiloxane physical blending liquid, totaling 88 grams, named liquid C.
[0044] (3) Preparation of inorganic sunscreen powder of aluminum hydroxide: Cosmetic grade aluminum hydroxide was processed with a colloid mill JML-50 to prepare a fine powder of about 50 microns, and 12 grams was weighed and named powder D.
[0045] (5) Preparation of inorganic sunscreen powder containing aluminum hydroxide: 12 g of the above-mentioned micron-sized fine powder aluminum hydroxide, 6 g of nano-sized titanium dioxide and 4 g of nano-sized zinc oxide were transported to a colloid mill JML-50, mixed under the action of mechanochemical force, baked in an oven at 100°C for 1 h, and then calcined at 500°C for 0.5 h for dehydration. The mixture was then dissociated and homogenized by impact with a high-pressure airflow of 0.6 MPa to obtain 18 g of inorganic sunscreen powder containing aluminum hydroxide with extremely high uniformity, named powder E.
[0046] (6) Preparation of physical composition of sunscreen silicone oil: In a 120 ml high-quality stainless steel reactor with stirring, 88 kg of organic sunscreen polydimethylsiloxane physical blending liquid C were added, 18 kg of the above-mentioned inorganic sunscreen powder E containing aluminum hydroxide was scattered into three batches and mixed evenly, 2 g of spermaceti PEG / PPG-10 / 1 polydimethylsiloxane was added, the temperature was raised to 62°C after mixing evenly, the speed was controlled at 280 rpm and stirred for 3 h until it reached a homogeneous and highly viscous state, 0.4 g of dextrin palmitate was dispersed and added, the speed was controlled at 100 rpm and stirred for 1 h, and the sunscreen silicone oil physical composition was obtained by cooling to room temperature, a total of 108.5 kg, named sunscreen silicone oil physical composition F.
[0047] Comparative Example 2: Preparation method of sunscreen skin care lotion: The refreshing composition in the formula of Example 2 is replaced with the sunscreen silicone oil physical composition F of Comparative Example 1, and the formula is as follows: 50 g of the sunscreen silicone oil physical composition F of Comparative Example 1, Vinyl Dimethicone / Methicone Silsesquioxane Crosspolymer 1g, Cetyl PEG / PPG-10 / 1 polydimethylsiloxane 2 grams, Diethylamino Hydroxybenzoyl Hexyl Benzoate 3g, Triethoxycaprylylsilane 2 g, Isostearic acid 1g, Butanediol 4g, Methyl Methacrylate Crosspolymer 3 g, Disteardimethylammonium hectorite 3 grams, 2 g triethyl citrate, VP / hexadecene copolymer 0.6 g, PEG-10 Dimethicone 2g, Phenoxyethanol 0.3 g, Ethylhexylglycerin 2 g, 1,3-propylene glycol 2 g, MAGNOLIA BIONDII flower extract 0.6g, Bisabolol 0.2 g, Dipotassium glycyrrhizinate 0.2 g, 0.3 g of p-hydroxyacetophenone, Tetrahydromethylpyrimidine carboxylic acid 0.2 g, Xanthan gum 0.1 g, 24 grams of purified water, The process conditions and operation steps are the same as those in Example 1 to prepare a sunscreen skin care lotion.
[0048] The performance of the products prepared in Example 2 and Comparative Example 2 of the present invention was tested.
[0049] Evaluation 1. Sunscreen effect test Sunscreen effect human body test: Sun Protection Factor (SPF): Also known as the Sun Protection Factor, it shows the sun protection effect of sunscreen products. The larger the SPF value, the better the sun protection effect. It is determined based on the minimum erythema dose (MED) of the skin. After using sunscreen products, the minimum erythema dose of the skin will increase.
[0050] Sun protection factor (SPF): The ratio of the MED required to cause erythema on the skin protected by the sunscreen cosmetic to the MED required to cause erythema on the unprotected skin is the SPF of the sunscreen cosmetic. It can be expressed as follows: SPF=MED of skin protected with sunscreen cosmetics / MED of unprotected skin.
[0051] Note: Minimal erythema dose (MED) refers to the minimum dose of ultraviolet radiation required to cause a clearly visible erythema on the skin, covering most of the irradiation area (J / m 2 ) or minimum time (seconds).
[0052] The SPF index is suitable for evaluating the protection against UVB.
[0053] Sunscreen cosmetics long-wave ultraviolet protection index (PFA value): also known as UVA protection index. When UVA in sunlight irradiates the skin, it mainly produces the physiological effect of skin darkening, which is measured by the minimum persistent darkening dose (MPPD). MPPD is the minimum ultraviolet radiation dose or the shortest irradiation time required to produce slight darkening of the skin on the entire irradiated area 2 to 4 hours after irradiation.
[0054] PFA = MPPD of skin protected with sunscreen cosmetics / MPPD of unprotected skin.
[0055] The sunscreen skin care lotions of Example 2 and Comparative Example 2 were selected, and the sunscreen effects of the products were tested according to the sun protection index test method (human body method) of sunscreen cosmetics in the "Technical Specification for Safety of Cosmetics" (2015 edition). The test results are shown in Table 1.
[0056] Table 1. Sunscreen effect test results sample SPF PFA Invention Example 2 Highly Effective Sunscreen Skin Care Lotion 50.8 16.5 Comparative Example 2 Sunscreen Skin Care Lotion 42.2 11.2 It can be seen from Table 1 that the sun protection index of the high-efficiency sunscreen skin care lotion prepared in Example 2 of the present invention can reach up to SPF50+PA+++, and the sun protection index of the sunscreen skin care lotion in Comparative Example 2 is significantly lower than that in Example 2.
[0057] Evaluation 2. Skin comfort and smoothness The basic performance of the high-efficiency sunscreen skin care lotion prepared in Example 2 of the present invention and the sunscreen skin care lotion sample of Comparative Example 2 in terms of skin feel was measured, and the measurement results are shown in Table 2. From the test results in Table 2, it can be seen that the sample of Example 2 of the present invention is better than Comparative Example 2 in terms of skin feel smoothness index.
[0058] Table 2. Determination of core indexes of skin smoothness
[0059] Evaluation 3. Skin stickiness and resistance The mechanical data related to combing properties of the high-efficiency sunscreen skin care lotion of Example 2 of the present invention and the sunscreen skin care lotion of Comparative Example 2 after hair soaking and then blow-drying were tested by a tensile tester method, and their stickiness and blocking properties on the skin were indirectly inferred.
[0060] (1) Overview The tensile tester is a test instrument specially used for evaluating the combing performance of hair. It uses a standard comb to imitate the action of combing hair by humans, combs a bunch of hair and records it by the terminal. When the comb passes through the hair fiber, it shows the force (unit: gf) loaded within the specified displacement (unit: mm) when it overcomes the resistance of the hair. By testing the change index of the combing force of the hair bundle before and after the sample is soaked, the stickiness of aloe vera gel can be indirectly inferred.
[0061] (2) Materials and methods (2.1) Main instruments and materials Tensile force meter; Constant temperature and humidity incubator; Several hair bundles: length 50cm, weight about 16g; Sunscreen skin care lotion: The high-efficiency sunscreen skin care lotion of Example 2 of the present invention and the sunscreen skin care lotion of Comparative Example 2 are both made into 10% water-diluted dispersed emulsions using an ultrasonic dispersing device.
[0062] (2.2) Hair bundle pretreatment Prepare several hair bundles of the same length (50 cm) and weight (about 16 g). First, wash them twice with 40°C tap water; then place the hair bundles in a beaker containing 5 g of sodium dodecyl sulfate and 1000 mL of water heated to 80°C and soak; then place the beaker in a constant temperature and humidity chamber at 45°C for two hours; finally, rinse with tap water until there is no foam, and dry naturally.
[0063] Sunscreen lotion sample treatment: weigh 4g of the diluted and dispersed emulsion sample of sunscreen lotion, rub it on the treated hair until it is uniform, let it stand for 30 minutes, rinse the hair with tap water, and blow it with a natural wind hair dryer for thirty minutes until it is almost dry.
[0064] (2.3) Combing test The dry combing properties of hair bundles treated with water-diluted dispersed emulsion samples of sunscreen skin care lotion were measured on a tensile tester.
[0065] ① Connect the host power supply, turn on the computer, and preheat the instrument for more than half an hour; ② Collect all the samples that make up the test sample and mark each sample; open the software, create a new sample, select the test method, and name the new sample; ③ Use a plastic comb to comb your hair first, then use a suitable clamp to fix the hair sample to be tested, and place the hair bundle naturally in the middle of the comb; ④After completing the calibration and zeroing of the instrument, start testing the hair bundle, stretch the hair bundle at a speed of 300mm / min, displace 200ram, and take the load value between 100 and 200mm. In order to reduce the measurement error caused by different hair bundles, repeat the test 5 times on the same hair bundle and take the average value (the program automatically records the data and calculates the average value).
[0066] (3) Results and discussion This test mainly examines the effects of the high-efficiency sunscreen skin care lotion of Example 2 of the present invention and the sunscreen skin care lotion of Comparative Example 2 on the combing properties of hair. The combing forces of dry hair are compared by testing with a tensile tester and recording the average load values (gf) of the hair bundles treated with the two diluted emulsion samples of sunscreen skin care lotion water. The data results are detailed in Table 3.
[0067] Table 3
[0068] It can be seen from Table 3 that the average dry combing load (gf) of the hair after treatment with the sunscreen skin care lotion in Example 2 of the present invention is significantly lower than that of the sunscreen skin care lotion in Comparative Example 2, which indirectly indicates that the sticky blocking force of the product of the present invention after being applied to the skin is extremely small, and the skin does not feel rough and astringent.
[0069] Evaluation 4. Patch test Test substance: The sample prepared in Example 2 was subjected to a patch test to detect its potential to cause adverse reactions on human skin.
[0070] Subjects: 38 subjects, including 18 males and 20 females, aged 20-40 years old, were selected as volunteers. Standard test method: Use a syringe to take 0.03mL of sample and place it in the drug chamber of the spot test tape. Immediately apply the spot test tape with the sample to the normal skin of the left forearm from the bottom, and press the drug chambers one by one to expel air and evenly distribute the test substance. Mark the test site for observation. The blank control group is for subjects who do not use the product.
[0071] Result analysis: After 24 hours, the patch test tape was removed, and the skin reaction was observed after half an hour, 24 hours, and 48 hours. The results of the skin reaction were recorded and analyzed according to the CTFA guidelines.
[0072] The identification criteria for skin irritation test are shown in Table 4 below.
[0073] Table 4. Skin irritation test identification standard table
[0074] The test results are shown in Table 5 below.
[0075] Table 5. Skin irritation test results
[0076] It can be seen from Table 5 that the high-efficiency sunscreen skin care lotion prepared in Example 2 of the present invention does not cause irritation and has good safety.
[0077] Evaluation 5. After application, the skin showed improvements in core beauty data such as increased elasticity, fine pores, reduced number and volume of crow's feet, etc. The skin elasticity improvement / anti-wrinkle / pore shrinkage / moisturizing indexes of the high-efficiency sunscreen skin care lotion of Example 2 of the present invention and the sunscreen skin care lotion of Comparative Example 2 were compared and tested using a testing instrument (VISIA-CR Corneometer CM825 Cutometer MPA585 Primos), as shown in Table 6 for details.
[0078] Table 6
[0079] Note: For this group of subjects (16 people), the high-efficiency sunscreen skin care lotion of Example 2 of the present invention was used once on the skin on the left side of the face, and at the same time, the sunscreen skin care lotion of Comparative Example 2 was used on the skin on the right side of the face.
[0080] In summary, the high-efficiency sunscreen skin care lotion of Example 2 of the present invention is significantly superior to the sunscreen skin care lotion of Comparative Example 2 in terms of core skin rejuvenation and skin care beauty data such as improved elasticity, refined pores, reduced number of crow's feet and reduced volume of crow's feet.
Claims
1. A method for preparing a refreshing composition, characterized in that The following steps are involved: (1) Preparation of a super acid catalyst: Phosphorus pentoxide and crystalline aluminum sulfate are uniformly mixed and calcined to obtain a super acid catalyst; (2) Preparing an organic sunscreen dispersion: heating ethylhexyl methoxycinnamate, butyl octanol salicylate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazone, and dibasic acid ester and uniformly mixing with butylated hydroxytoluene to obtain a liquid A; (3) Preparing an adhesive polydimethylsiloxane: octamethylcyclotetrasiloxane and the above-mentioned liquid A are stirred and mixed to obtain liquid B; liquid B is reacted with a superacid catalyst and hexamethyldisiloxane in sequence to obtain an adhesive polydimethylsiloxane finished liquid, which is named liquid C; (4) Preparing a hydrated alumina dispersion slurry: reacting high-purity sodium aluminum carbonate with an aqueous sodium hydroxide solution to obtain a hydrated alumina dispersion slurry containing sodium aluminate, which is named as liquid D; (5) Preparation of smooth modified inorganic powder: Nano-sized titanium dioxide and nano-sized zinc oxide are added to liquid D in batches, and a layer of gel Al(OH)3 is deposited on the surface of nano-sized titanium dioxide and zinc oxide particles. After further post-treatment, a modified nano-sized titanium dioxide / zinc oxide smooth inorganic sunscreen powder uniformly loaded with gel aluminum hydroxide / γ-aluminum trioxide fusion is obtained, which is named powder E. (6) Preparation of a refreshing composition: Powder E is added to liquid C, and cetyl PEG / PPG-10 / 1 polydimethylsiloxane and dextrin palmitate are added, and the refreshing composition is obtained after stirring.
2. The method for preparing the refreshing composition according to claim 1, characterized in that: In step (1), the mass ratio of phosphorus to sulfur in the obtained superacid catalyst is 1:(0.5-0.7).
3. The method for preparing the refreshing composition according to claim 1, characterized in that: In step (2), the mass ratio of ethylhexyl methoxycinnamate, butyl octanol salicylate, bis-ethylhexyloxyphenol methoxyphenyl triazine, and ethylhexyl triazone is 8:(5-6):(2.5-3):(1.5-2).
4. The method for preparing the refreshing composition according to claim 1, characterized in that: In step (2), the dibasic acid ester is a mixture of dibutyl adipate and diisopropyl sebacate, and the mass ratio of dibutyl adipate to diisopropyl sebacate is 6:(5-8).
5. The method for preparing the refreshing composition according to claim 1, characterized in that: In step (5), the liquid D is added with nano-sized titanium dioxide and nano-sized zinc oxide in batches under the condition of bubbling with high-purity carbon dioxide, and the nano-sized titanium dioxide and zinc oxide particles with gel Al(OH)3 deposited on the surface are successively dehydrated, dissociated and homogenized to obtain the powder E.
6. The method for preparing the refreshing composition according to any one of claims 1 to 5, characterized in that: The refreshing composition comprises the following components: Powder E 13~28 parts by weight, Liquid C 50~90 parts by weight, 1-3 parts by weight of cetyl PEG / PPG-10 / 1 polydimethylsiloxane, Dextrin palmitate 0.3-0.5 parts by weight.
7. The method for preparing the refreshing composition according to claim 6, characterized in that: The powder E is prepared from the following components: Liquid D 55~110 parts by weight, 5-10 parts by weight of nano-sized titanium dioxide, 3-8 parts by weight of nano zinc oxide; Wherein, the feed liquid D is prepared from the following components: 5-10 parts by weight of high-purity sodium aluminum carbonate, 50 to 100 parts by weight of 2% to 5% sodium hydroxide aqueous solution.
8. The method for preparing the refreshing composition according to claim 6, characterized in that: The feed liquid C is prepared from the following components: Liquid B 70~110 parts by weight, 4 to 5 parts by weight of superacid catalyst, 5-10 parts by weight of hexamethyldisiloxane, 200-300 parts by weight of water; Wherein, feed liquid B is prepared from the following components: Liquid A 30~50 parts by weight, 40-60 parts by weight of octamethylcyclotetrasiloxane.
9. A sunscreen skin care product using the refreshing composition according to any one of claims 1 to 8, characterized in that: According to weight parts, it includes the following components: 45-55 parts of refreshing composition, Vinyl dimethicone / methylsiloxane silsesquioxane crosspolymer 1-3 parts, 1~2 parts of cetyl PEG / PPG-10 / 1 polydimethylsiloxane, 2-3 parts of diethylamino hydroxybenzoyl hexyl benzoate, 2~4 parts of triethoxycaprylylsilane, 1~3 parts of isostearic acid, 4-7 parts of butanediol, 2-3 parts of methyl methacrylate cross-linked polymer, 1-3 parts of disteardimethylammonium hectorite, 1~2 parts of triethyl citrate, VP / hexadecene copolymer 0.5-0.8 parts, PEG-10 polydimethylsiloxane 1~3 parts, Phenoxyethanol 0.1~0.3 parts, 1~2 parts of ethylhexylglycerin, 1,3-propylene glycol 1~2 parts, 0.3~0.6 parts of Flos Miscanthus extract, 0.1~0.3 parts of bisabolol, 0.1~0.2 parts of dipotassium glycyrrhizinate, 0.2~0.3 parts of p-hydroxyacetophenone, 0.1-0.2 parts of tetrahydromethylpyrimidine carboxylic acid, Xanthan gum 0.08~0.12 parts, 20~25 parts of water.
10. A method for preparing the sunscreen skin care product according to claim 9, characterized in that The following steps are involved: (1) Vinyl dimethicone / polymethicone silsesquioxane crosspolymer and cetyl PEG / PPG-10 / 1 dimethicone are mixed and stirred until uniformly mixed, and diethylamino hydroxybenzoyl hexyl benzoate is added, and stirred and mixed until uniformly mixed at room temperature to obtain an oil phase G; Triethoxycaprylylsilane, triethyl citrate and isostearic acid are stirred and mixed and heated to 60-65°C and stirred and mixed to form a liquid state, VP / hexadecene copolymer and methyl methacrylate cross-linked polymer are added in batches and stirred and mixed for at least 1 hour until a homogeneous thick liquid state is formed, dispersing disteardimethylammonium hectorite and stirring and mixing for at least 2 hours until a homogeneous state is formed, and then adding it to the refreshing composition, controlling the rotation speed at 200-300 rpm and stirring for at least 3 hours until a homogeneous high viscosity state is formed, to obtain oil phase H; (2) Add PEG-10 polydimethylsiloxane to two-thirds of the total amount of water under stirring and dissolve until it becomes translucent. Add dipotassium glycyrrhizinate and stir until it becomes nearly transparent. Add phenoxyethanol ethylhexylglycerin and p-hydroxyacetophenone and heat to 60-70°C for use to obtain aqueous phase I. (3) Disperse xanthan gum in 1,3-propylene glycol and butylene glycol, stir until it becomes nearly transparent and highly viscous, add one third of the total amount of water, mix well, add tetrahydromethylpyrimidine carboxylic acid, flos dasyphylla extract and bisabolol, mix well and set aside to obtain aqueous phase J; (4) Under stirring conditions, control the temperature at 60-75°C, slowly add the aqueous phase I into the oil phase H, and stir for at least 10 minutes until the system reaches the initial state of a high-viscosity W / O emulsion. Then control the speed at 3000-5000 rpm for homogenization for at least 15 minutes to obtain a homogenous high-gloss and high-viscosity W / O emulsion. Cool to 35-38°C, add the aqueous phase J under stirring conditions, and then control the speed at 3000-5000 rpm for homogenization for at least 10 minutes until it reaches a high-gloss homogenous emulsion state. Then add the oil phase G, control the speed at 300-400 rpm for stirring for at least 30 minutes, homogenize the high-gloss and high-viscosity W / O emulsion, and age it for 24 hours to obtain the target product, a sunscreen skin care product.
Citation Information
Patent Citations
Low-irritation sunscreen lotion and preparation method thereof
CN112370406A
Plant extract hair conditioner and preparation method thereof
CN112618416A
Full-wave-band ultraviolet sunscreen lotion and preparation method thereof
CN113332213A
Refreshing and mild physical sunscreen lotion for infants and children and preparation method of refreshing and mild physical sunscreen lotion
CN116763667A
Organosilicone elastomer with regular structure and preparation method and application thereof
CN117700753A